On Some Properties Of Solutions Of A Three-Dimentional Linear Homogeneous System Of Differential Equations With A Positive Coefficients - Sahakyan, Georgi; Ohanyan, A.
The paper considers the some properties of solutions of a three-dimentional linear homogeneous system of differential equations with a postive and continuous on the whole numerical line coefficients. Աշխատանքում ամբողջ թվային առանցքի վրա անընդհատ և դրական գործակիցներով եռաչափ գծային համասեռ դիֆերենցիալ հավասարումների համակարգերի համար դիտարկվում են լուծումների որոշ հատկությունները: В работе рассматриваются свойства решений трехмерной линейной однородной системы дифференциальных уравнений с положительными и непрерывными на всей числовой оси коэффициентами.
Keywords: Mathematics